Por uma Governança Democrática : Triangulo Mineiro - Brasil - Uberlândia - Barroso, Frank; Muno Colesanti, Marlene Teresinha de
The City Educator Program is articulated with PROEX-Pro - Deanship Culture and Student Affairs through the Directorate of Extension, along with the Institute of Geography, Faculty of Architecture, Urban Planning and Design Institute and the City Futura Pro. Program is conducted since 2008 by the Federal University of Uberlândia and Motion City Futura. The outreach program aims to promote democratic governance and smart planning municipal and regional level, enabling public and social (government technicians, law enforcement officers, and civil society leaders) seeking implementation of legal instruments, urban and tributaries in the counties of Araguari and Uberlândia, established in the City Statute and Master Plans, and the Fiscal Responsibility, Social Rights established by the Constitution, and all the instruments of social control in the municipalities involved. The methodology includes content developed through dynamic, research participant, group work and exposure dialogue. The results were relevant to holding the Course on Urban Management and Sustainable Democratic, Uberlândia A Forum for Sustainable Leadership Training Course Ethical and Sustainable, Community Workshops Seminars in Neighborhoods assessment; Map Workshop Speaker, Research Participants, Seminars and Interactive Campaigns Mobilization office in the territory. Were produced articles, reports and reflections that are public in book form. At the end of the implementation of program activities, the municipal governments, entities and non-governmental organizations as well as citizens who, directly or indirectly, involved with the program, attended the final seminar where, besides the presentation of results, was made, collectively, evaluation and assessment of all activities
O Programa Cidade Educadora é articulado com a PROEX- Pró - Reitoria de Extensão, Cultura e Assuntos Estudantis, através da Diretoria de Extensão, juntamente com o Instituto de Geografia, a Faculdade de Arquitetura, Urbanismo e Design e o Instituto Pró Cidade Futura. Programa é realizado desde 2008 pela Universidade Federal de Uberlândia e o Movimento Cidade Futura. O programa de extensão tem como objetivo promover a governança democrática e inteligente do território municipal e regional, capacitando agentes públicos e sociais (técnicos governamentais, operadores do direito, lideranças e sociedade civil) visando implementação dos Instrumentos jurídicos, urbanísticos e tributários, nos municípios de Araguari e Uberlândia, estabelecidos no Estatuto da Cidade e nos Planos Diretores, além da Responsabilidade Fiscal, dos Direitos Sociais estabelecidos na Constituição Federal, e todos os instrumentos de controle social nos municípios envolvidos. A metodologia contempla conteúdos desenvolvidos por intermédio de dinâmicas, da pesquisa participante, trabalhos em grupo e exposição dialogada. Os resultados relevantes foram a realização do Curso de Gestão Urbana Democrática e Sustentável, Fórum por Uma Uberlândia Sustentável, Curso de Formação de Lideranças Éticas e Sustentáveis; Oficinas Comunitárias nos Bairros Seminários de avaliação; Oficina de Mapa Falante, Pesquisa participantes, Seminários Interativos e Campanhas de Mobilização social no território. Foram produzidos artigos, relatórios e reflexões que serão publicas em livro. Ao final da execução das atividades do programa, os poderes públicos municipais, as entidades e organizações não governamentais, bem como os cidadãos que, diretamente ou indiretamente, envolveram-se com o programa, participaram do Seminário final onde, além da apresentação dos resultados, foi feita, de forma coletiva, a avaliação e o balanço de todas as atividades realizadas^lpt
Keywords: Governance; Democracy; Educating city; Governança; Democrática; Cidade educadora^lpt